The Development of Kampung Bekelir as a Tourist Attraction in Tangerang City - Willie Natanael; Sri Pujiastuti (The Postgraduate School of Tourism Sahid Polytechnic, 2026)
Purpose : This study aims to analyze the potential, opportunities, and challenges in developing Kampung Bekelir as a tourist attraction in Tangerang City. Research methods : This research used a qualitative approach with purposive sampling. Data were collected through in-depth interviews, field observations, and documentation studies involving key informants such as community leaders, Kampung Bekelir managers, MSME actors, and tourists. The data were analyzed using the 4A framework (Attraction, Accessibility, Amenities, Ancillary Services) combined with SWOT analysis. Results and discussion : The results show that Kampung Bekelir has strengths such as a unique visual identity, strategic location, and strong community support. However, it also faces weaknesses such as faded murals, an inactive tourism awareness group, and limited tourist facilities. Opportunities include collaboration with artists, government and CSR support, and the development of cultural and creative attractions, while threats consist of declining community participation, loss of sponsorship, and competition with other destinations. Implication : The research provides insights for local governments, community groups, and tourism stakeholders to optimize the development of Kampung Bekelir as a leading tourist attraction in Tangerang City and to strengthen community-based tourism initiatives in urban areas. Keywords : community-based tourism, Kampung Bekelir, tourist attraction, creative tourism, Tangerang City